2018
DOI: 10.1002/joec.12092
|View full text |Cite
|
Sign up to set email alerts
|

Linking Individual Value Orientations to Employee Attitudes: An Exploratory Analysis

Abstract: This study tested the relationships of individualism, power distance, and mastery orientation to 2 employee attitudes (organizational trust and organizational commitment) that are associated with employees' psychological benefits within the organization. Results from university employees (N = 706) showed that individualism negatively, whereas mastery positively, related to trust and commitment. Power distance positively related to trust only. The moderating role of mastery was also identified. These findings c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Furthermore, the inclusion of paternalism as an additional dimension makes Dorfman and Howell [2] instrument particularly suitable to conduct cultural research in societies where such cultural construct has been identified as fundamental in understanding how culture influences work related issues, as is the case of Latin America, India, Turkey, the Middle East and China among other regions and countries [25,26]. Finally, Dorfman and Howell's scales have the advantage of being designed to capture data at an individual unit of analysis facilitating research focusing on the association between individual employees' cultural values and job-related attitudes (e.g., [27,28]). That is, the Dorfman and Howell [2] adaptation of Hofstede's national culture dimensions allows for the study of cultural orientation at the individual level with a reliable psychometric instrument [29].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the inclusion of paternalism as an additional dimension makes Dorfman and Howell [2] instrument particularly suitable to conduct cultural research in societies where such cultural construct has been identified as fundamental in understanding how culture influences work related issues, as is the case of Latin America, India, Turkey, the Middle East and China among other regions and countries [25,26]. Finally, Dorfman and Howell's scales have the advantage of being designed to capture data at an individual unit of analysis facilitating research focusing on the association between individual employees' cultural values and job-related attitudes (e.g., [27,28]). That is, the Dorfman and Howell [2] adaptation of Hofstede's national culture dimensions allows for the study of cultural orientation at the individual level with a reliable psychometric instrument [29].…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple studies about the relationship between individual level perceptions of cultural dimensions and individual level attitudinal and behavioral outcomes using Dorfman and Howell [2] scales. For example, Jiang [28] showed that individualism negatively correlated to trust and commitment whereas task mastery correlated positively, while power distance is related to trust only. Wu [31] measured Hofstede's cultural dimensions, using Dorfman and Howell [2] instrument, and concluded that work-related cultural values in a specific culture are not static and change over time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Jiang (2018) show that individual power distance orientation is associated with AC when one's mastery orientation was low but not when it was high.…”
Section: Organizational Commitmentmentioning
confidence: 99%